The effective local therapy of vaginal discharge - A L Tikhomirov (IP Berlin A.V., 2015)
In the article from the contemporary positions the effectiveness of the local treatment of vaginal discharge is examined. Is evaluated the role of the combined preparations at treatment and preventive maintenance of vaginal infections.